ECM stiffness regulates glial migration in Drosophila and mammalian glioma models. - Kim, S.N.; Jeibmann, A.; Halama, K.; Witte, H.T.; Wälte, M.; Matzat, T.; Schillers, H.; Faber, C.; Senner, V.; Paulus, W.; Klämbt, C. (Development, 2014)
Cell migration is an important feature of glial cells. Here, we used the Drosophila eye disc to decipher the molecular network controlling glial migration. We stimulated glial motility by pan-glial PDGF receptor (PVR) activation and identified several genes acting downstream of PVR. Drosophila lox is a non-essential gene encoding a secreted protein that stiffens the extracellular matrix (ECM). Glial-specific knockdown of Integrin results in ECM softening. Moreover, we show that lox expression is regulated by Integrin signaling and vice versa, suggesting that a positive-feedback loop ensures a rigid ECM in the vicinity of migrating cells. The general implication of this model was tested in a mammalian glioma model, where a Lox-specific inhibitor unraveled a clear impact of ECM rigidity in glioma cell migration.